PENGARUH KEDISIPLINAN GURU DAN MOTIVASI KERJA TERHADAP KINERJA GURU SMA SE KABUPATEN GRESIK - Dina, Syafitri Rahmadina Purima; Nursalim, Mochamad; Kamidi, Amrozi; Widiyanah, Ima; Trihantoyo, Syunu; Karwanto, Karwanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the effect of teacher discipline and work motivation on teacher performance. The research method used a quantitative method. The population of the study was all state high school teachers in Gresik. The research sample was 319 respondents. The research instrument used a questionnaire with a Likert scale. The data analysis technique used multiple linear analysis with the help of SPSS. The results of the study showed that the work motivation of high school teachers in Gresik Regency had an average score of 4.13, which is included in the sufficient category. The work discipline of high school teachers in Gresik Regency had an average score of 2.68, which is included in the sufficient category. The performance of high school teachers in Gresik Regency had an average score of 7.38, which is included in the very high category. Work discipline has a significant positive effect on the performance of high school teachers in Gresik Regency. Work motivation has a significant positive effect on the performance of high school teachers in Gresik Regency. Work discipline and work motivation have a significant positive effect on the performance of high school teachers in Gresik Regency.